2003
DOI: 10.3354/meps261257
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation kinetics and exposure pathways of inorganic mercury and methylmercury in a marine fish, the sweetlips Plectorhinchus gibbosus

Abstract: We experimentally determined the assimilation efficiency (AE) of ingested prey, the uptake-rate constant from the aqueous phase, and elimination-rate constant of both inorganic Hg (Hg [II]) and methylmercury (MeHg) in a marine predatory fish, the sweetlips Plectorhinchus gibbosus, using radiotracer techniques. The AE of Hg(II) and MeHg ranged between 10 and 27% and between 56 and 95%, respectively, for 3 different prey (copepods, silverside, and brine shrimp). The ingestion rate of the fish did not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
111
6
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 56 publications
19
111
6
1
Order By: Relevance
“…(Wang and Wong, 2003 Several studies have demonstrated that Hg concentrations in the muscles of marine organisms proportionally increase with size and age (Lange et al, 1994;Burger et al, 2001;Green and Knutzen, 2003;Simonin et al, 2008). Moreover, Hg de-toxification rates appear negatively correlated with the fish size (Trudel and Rasmussen, 1997), supporting a potential correlation between Hg levels and size/age in the organisms.…”
Section: Mercury Bioaccumulation Effects: Length/age Vs Hgt Contentmentioning
confidence: 91%
“…(Wang and Wong, 2003 Several studies have demonstrated that Hg concentrations in the muscles of marine organisms proportionally increase with size and age (Lange et al, 1994;Burger et al, 2001;Green and Knutzen, 2003;Simonin et al, 2008). Moreover, Hg de-toxification rates appear negatively correlated with the fish size (Trudel and Rasmussen, 1997), supporting a potential correlation between Hg levels and size/age in the organisms.…”
Section: Mercury Bioaccumulation Effects: Length/age Vs Hgt Contentmentioning
confidence: 91%
“…Mercury belongs to the group of elements that induces metallothionien production, which detoxifies the metal (Pulsford et al, 1992). On this way, some studies have revealed that high and prolonged exposure can overwhelm the defense mechanisms, and excretion may not keep pace with accumulation (Wang and Wong, 2003); thus mercury remained available for incorporation in the otolith, and its incorporation would reflect both concentration and exposure level, like other authors have reported (Geffen et al, 1998). At the same time, some studies found that the Pb and Cd otoliths content, are more likely related to the fish environment than to physiological processes, and their concentrations are associated with anthropogenic sources and is not correlated with pH, salinity or other environmental factors (Köck et al, 1996;Ranaldi and Gagnon, 2008a).…”
Section: Resultsmentioning
confidence: 99%
“…Some elements may be metabolized, some sequestered so that they become biologically inactive, and others detoxified by conversion into other phases which are then excreted (Xu andWang, 2002, Wang andWong, 2003). Mercury belongs to the group of elements that induces metallothionien production, which detoxifies the metal (Pulsford et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…This difference was caused by differences between the bio-dynamics of Hg (II) and MeHg in each species [51,[55][56][57]. The lower ratio of MeHg to Hg in crabs suggests decreased bioaccumulation of MeHg and less toxicity for higher trophic levels [58].…”
Section: Biotamentioning
confidence: 99%
“…The lower ratio of MeHg to Hg in crabs suggests decreased bioaccumulation of MeHg and less toxicity for higher trophic levels [58]. Factors, such as habitat type (shallow hard-bottom intertidal or sometimes subtidal habitats) or differences in prey availability, such as macroalgae, salt marsh grasses and small invertebrates between upstream and downstream areas, could explain the difference in the [Hg] and [MeHg] in crab samples [51,[55][56][57][58][59].…”
Section: Biotamentioning
confidence: 99%